Health care system barriers to vaginal birth after cesarean section: A qualitative study - Mahboobeh Firoozi; Fatemeh Tara; Mohammad Reza Ahanchian; Robab Latifnejad Roudsari (Wolters Kluwer Medknow Publications, 2020)
Background: Approximately half of mothers give birth by cesarean section in Iran and two-thirds of them are repeated cesareans. Repeated cesarean is threatening for the mothers and newborns and not compatible with fertility policies in Iran. Vaginal Birth After Cesarean (VBAC) is a reasonable strategy but its prevalence is very low due to some barriers. The aim of this study was to explore barriers to VBAC in health care system. Materials and Methods: In this qualitative study, 26 semi-structured individual interviews with maternity care providers and mothers with prior cesarean section as well as one focus group discussion with maternity care providers were conducted. Interviews and focus group discussions were tape-recorded, transcribed verbatim and analyzed with conventional content analysis developed by Graneheim and Lundman using MXQDA10 software. Results: Barriers to VBAC in health care system identified in the main category of "the climate of restriction, fear and discourage" and eight subcategories including: "defective access to specialized services," "insufficient encouragement system," "modeling in cesarean section," "physician-centeredness in VBAC," "fear of legal responsibilities," "imposed policies," "marginalization of midwives," and "unsupportive birth team." Conclusions: To remove barriers of VBAC in health care system, appropriate strategies including establishment of specialized VBAC counseling centers, performance-based incentive policies, cultural development and promotion of natural childbirth, promoting of teamwork culture, shared decision making, improvement of knowledge and skills of maternal care providers and implementation of clinical guidelines, should be considered. Future research could be focused on the effect of implementing these strategies to decrease repeat cesarean section rate.